أهمية نظم الاستنتاج الضبابي في إيجاد مستويات الازدحام على الطرق الشريانية - شذى أسعد; علي شقيره (Tishreen University, 2019)
يعتبر الإزدحام المروري من أكثر مشاكل النقل الحضري وأكثرها تعقيدًا، إذ أنه ظاهرة ديناميكية تتطلب نهجًا متكاملاً ومتعدد المستويات لفهمها، ورؤية استراتيجية لإدارتها بعيدًا عن الطرق التقليدية، وذلك بإيجاد مقياس للإزدحام يساعد على فهم سلوك الحركة على الشوارع الشريانية، وإيجاد علاقة تفاعلية بين بين شبكة الطرق والمستخدمين وأنظمة المرور. يبرز من خلال هذا البحث الدور الحيوي لمنهجية الاستنتاج الضبابي لتقييم مستويات الازدحام المروي على القطاعات والطرق الشريانية ضمن شبكة الطرق المدينية، حيث تم توضيح الفرق بين الطرق التقليدية التي تعتمد على مقاييس فردية، وطريقة الاستنتاج الضبابي التي تعتمد على دمج عدة مقاييس فردية ضمن مقياس مركب لقياس مستويات الازدحام المروري. وهنا تم اتخاذ مقياس أداء السرعة كمثال عن المقاييس الفردية. حيث تم تقسيم الطريق المذكور إلى قطاعات بمسافات مختلفة وحساب السرعات اللحظية والمتوسطة والزمن اللازم لعبور كل قطاع، خلال ساعة الذروة وخارجها وثم حساب البارامترات والمؤشرات اللازمة لعملية المقارنة بين المنهجيتين، حيث في البداية تم قياس سرعة العربة خلال فترات ساعة الذروة بواسطة جهاز GPS بسيط، ثم استنتاج مستويات الازدحام من خلال مؤشر أداء السرعة، ثم مقارنتها مع مستويات الازدحام المحسوبة بطريقة الاستنتاج الضبابي، حيث تم انشاء موديل ضبابي عبر دمج مؤشرين هما: نسبة السرعة المنخفضة جدًّا، ومعدل سرعة الرحلة، وتبين وجود فروقات بين الطريقتين، مما يوضح أهمية استخدام المنطق الضبابي في المسائل المرورية، وخاصة الإزدحام المروري. Traffic congestion is one of the most complex and complex urban transport problems. It is adynamic phenomenon that requires an integrated and multi-level approach to understanding it and a strategic vision to manage it away from traditional methods by finding a measure of congestion that helps to understand traffic behavior on the arterial streets, Roads, users and traffic systems. This research highlights the vital role of the participatory conclusion methodology for assessing the levels of irrigated congestion on sectors and arterial roads within the urban road network, where the difference between traditional methods based on individual measurements and the fuzzy Inference method is based on the integration of several individual measurements into a composite scale Traffic congestion levels. Here, the measure of speed performance index was taken as an example of individual measures. This route was divided into sectors of different distances, calculation of the intraday and intermediate speeds and the time necessary to cross each sector during peak hour and beyond, and then calculating the parameters and indicators needed for the comparison between the two methodologies. The speed of vehicles were measured during peak hour periods by a simple GPS device, then the congestion levels were defined through the speed performance indicator, then compared to the calculated congestion levels through the fuzzy method. Fuzzy model was created by combining two indicators: very low speed ratio and the travel speed rate, and there are differences between the two methods, which illustrates the importance of using fuzzy logic in traffic issues, especially traffic congestion.